Pengaruh Marital Status Terhadap Kedisiplinan Kerja Dan Produktivitas Kerja (Studi Kasus Pada Pemerintah Daerah Kabupaten Sragen) - Rosadianto, Erdian Cahyo, Imron Rosyadi, S.E., M.Si (2016)
This study aims to determine the influence of marital status on work discipline and productivity of work in Local Government Sragen especially be true in some SKPD ie DPU and BKD Sragen. Based on the results of this study are expected to be feedback to improve work discipline and productivity of work for employees who are married or unmarried. The population of this research was the Civil Service Unit (SKPD) Sragen, who are willing to be the object of research is only 2 SKPD of as much as 63 SKPD with a total population of 69 employees from 365 employees in each SKPD are namely BKD and DPU. Based on the results of descriptive test showed that respondents who are married as many as 41 people with a percentage of 59.4% and the status of unmarried respondents were 28 people with a percentage of 40.6%. It can be concluded that the majority of respondents were married. Based on the survey results revealed that the Kolmogorov-Smirnov test values obtained Kolmogorov-Smirnov Z at 1.138 and Asym. Sig. amounted to 0.150, because the significance value> 0.05, it can be concluded the research data were normally distributed. H1 states there is influence of marital status on work discipline, H2 stating there is influence marital status on work productivity, H3 states there is work discipline effect on work productivity, H4 states the relationship work discipline on work productivity moderated by marital status. It can be concluded that all of this hypothesis is accepted. Keywords: Marital status, work discipline, work productivity.